2008
DOI: 10.1002/ijc.23683
|View full text |Cite
|
Sign up to set email alerts
|

The enhancer of zeste homolog 2 gene contributes to cell proliferation and apoptosis resistance in renal cell carcinoma cells

Abstract: The enhancer of zeste homolog 2 (EZH2) gene has been recently linked to human malignancies where it may serve as a new target for cancer therapy. Here, we analyzed EZH2 expression in primary renal cell carcinoma (RCC) specimens and in nontumorous tissue samples from adult kidney. EZH2 transcripts were detectable in all RCC specimens examined. Expression levels were significantly higher in tumor tissue (p 0.0001) than in samples from normal adult kidney. Moreover, inhibition of endogenous EZH2 expression in RCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 30 publications
0
39
1
Order By: Relevance
“…Previous studies have shown that epigenetic changes including differential expression of the histone methyltransferase EZH2 may be associated with drug resistance (17-18). A survey of over 400 ccRCC tumors from the TCGA data portal identified several changes in the methylation status of the lysine tails of histone 3 and the associated mutated genes with progression of disease to advance staged (19).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that epigenetic changes including differential expression of the histone methyltransferase EZH2 may be associated with drug resistance (17-18). A survey of over 400 ccRCC tumors from the TCGA data portal identified several changes in the methylation status of the lysine tails of histone 3 and the associated mutated genes with progression of disease to advance staged (19).…”
Section: Resultsmentioning
confidence: 99%
“…52 Knock-down of EZH2 reduces cell proliferation, 52 and causes apoptosis in a subset of RCC cell lines. 51, 52 Given the low mutation frequency of SMARCB1 it is unlikely that SMARCB1 was the determinant of sensitivity in these cell lines. Of note, the one cell line that did not undergo apoptosis in response to EZH2 knock-down, 769-P, 51 is BAP1 mutant.…”
Section: Therapeutic Implications Of Pbrm1 Loss In Ccrccmentioning
confidence: 98%
“…51, 52 Given the low mutation frequency of SMARCB1 it is unlikely that SMARCB1 was the determinant of sensitivity in these cell lines. Of note, the one cell line that did not undergo apoptosis in response to EZH2 knock-down, 769-P, 51 is BAP1 mutant. 18 EZH2 levels in ccRCC may have prognostic value, but these data are controversial.…”
Section: Therapeutic Implications Of Pbrm1 Loss In Ccrccmentioning
confidence: 98%
See 1 more Smart Citation
“…Increasing evidence has revealed that EZH2 has oncogenic properties, as an increased expression of EZH2 augments proliferation and invasion of cancer cells [9294], while depletion leads to a decline in cell proliferation, increased apoptosis, and inhibition of metastatic tumor growth in vivo [95, 96]. Overexpression of EZH2 has been associated with tumor progression and cancer aggressiveness in NSCLC [97].…”
Section: Mirna and Response To Cancer Therapymentioning
confidence: 99%